2017
DOI: 10.7554/elife.20142
|View full text |Cite
|
Sign up to set email alerts
|

APP modulates KCC2 expression and function in hippocampal GABAergic inhibition

Abstract: Amyloid precursor protein (APP) is enriched at the synapse, but its synaptic function is still poorly understood. We previously showed that GABAergic short-term plasticity is impaired in App knock-out (App-/-) animals, but the precise mechanism by which APP regulates GABAergic synaptic transmission has remained elusive. Using electrophysiological, biochemical, moleculobiological, and pharmacological analysis, here we show that APP can physically interact with KCC2, a neuron-specific K+-Cl- cotransporter that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 58 publications
6
69
0
Order By: Relevance
“…In extracellular hippocampal slice recordings from KCC2 +/− mice, spontaneous events displayed both increased amplitude and frequency, highlighting a potential difference in the effects of lower KCC2 expression between brain regions [Zhu et al, ]. However, we did not observe any change in mIPSC amplitude in the mPFC, despite the known action of KCC2 on chloride channels and expected effects on GABA signaling, and this effect is consistent with another study that recorded currents in the hippocampus, in which KCC2 protein expression was decreased by about 50%, although this was due to the knockout of amyloid precursor protein [Chen et al, ]. This could suggest that the observed effects on mEPSCs reflect the summed impact of KCC2 loss across circuits, rather than simply reflecting effects within the dmPFC pyramidal neurons themselves.…”
Section: Discussionsupporting
confidence: 90%
“…In extracellular hippocampal slice recordings from KCC2 +/− mice, spontaneous events displayed both increased amplitude and frequency, highlighting a potential difference in the effects of lower KCC2 expression between brain regions [Zhu et al, ]. However, we did not observe any change in mIPSC amplitude in the mPFC, despite the known action of KCC2 on chloride channels and expected effects on GABA signaling, and this effect is consistent with another study that recorded currents in the hippocampus, in which KCC2 protein expression was decreased by about 50%, although this was due to the knockout of amyloid precursor protein [Chen et al, ]. This could suggest that the observed effects on mEPSCs reflect the summed impact of KCC2 loss across circuits, rather than simply reflecting effects within the dmPFC pyramidal neurons themselves.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, we found that the level of GABA receptor subunit alpha 1 (GABARα1) was diminished in the absence of APP and in NPAS4-deficient neurons. This is in agreement with recent study showing that GABARα1 is particularly decrease in hippocampus of APP-/- mice (Chen et al 2017) correlating with a decrease in IPSC amplitude. But on the other hand, it suggests that increases in GABA release in APP-deficient models may not result in a net increase of inhibitory transmission, or at least there is a complex modulation of neuronal response to GABA.…”
Section: Discussionsupporting
confidence: 94%
“…APP was also described to play an important role in GABAergic inhibitory neurotransmission. APP deficiency reduces paired pulse depression (PPD) in mice (Seabrook et al, 1999) and affects GABA receptors expressions (Fitzjohn et al, 2000; Chen et al, 2017), while APP overexpression induces hyperexcitability due to GABAergic neurotransmission failure (Born et al, 2014). Recently, APP was associated with the GABA excitatory/inhibitory shift occurring in embryonic neurons (Doshina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in mRNA and protein expression suggest that NKCC1 and KCC2 are post-translationally modified. 21,22 KCC2 also plays a role in synapse stabilisation through cytoskeletal interactions that is independent of its chloride transporter function, 23,24 providing another possible mechanism by which a testosterone-mediated delay of KCC2 expression 4 leads to slower maturation of neural circuitry in males. Expression of KCC2 and NKCC1 is critical to early brain development and exhibits marked sex-specific postnatal developmental expression.…”
Section: Discussionmentioning
confidence: 99%